Public policy and economic inequality: The United States in comparative perspective - Timothy M. Smeeding (Luxembourg Income Study (LIS), 2004)
This article compares recent economic inequality in industrialized nations, largely those belonging to the Organization for Economic Cooperation and Development (OECD). This research finds the United States has the highest overall level of inequality of any rich OECD nation in the mid-1990s. It also finds that the increases in the dispersion of total household income in the United States have been as large as, or larger than, those experienced elsewhere between 1979 and 2000, despite the fact that the US began the period with the highest level of inequality. The authors also look at the trend in inequality within the United States using various series from published and unpublished data to examine exactly how US inequality changed over the past several decades. Next, the authors examine the effects of government policies and social spending efforts on inequality, finding that the United States has lesser effects than any other rich nation, and that both low spending and low wages have a great impact on the final income distribution, especially among the non-elderly. The authors then are in a position to answer a number of questions. What role does policy; therefore, play in the final determination of income inequality? Can these differences be explained by demography (more single parents; more immigrants; or more elders?) or can they be attributed to American institutions and lack of spending effort on behalf of low-income families? And finally, does inequality of before tax and benefit income itself have anything to do with low social spending?
Keywords: 330; Einkommensverteilung; Vergleich; USA; Welt